Toward "Pseudo-Haptic Avatars": Modifying the visual animation of Self-Avatar can simulate the perception of weight lifting - Gomez Jauregui, D. A.; Argelaguet, F.; Olivier, A. H.; Marchal, M.; Multon, F.; Lecuyer, A. (IEEE Transactions on visualization and computer graphics, 2014)
In this paper we study how the visual animation of a self-avatar can be artificially modified in real-time in order to generate different haptic perceptions. In our experimental setup, participants could watch their self-avatar in a virtual environment in mirror mode while performing a weight lifting task. Users could map their gestures on the self-animated avatar in real-time using a Kinect. We introduce three kinds of modification of the visual animation of the self-avatar according to the effort delivered by the virtual avatar: 1) changes on the spatial mapping between the user's gestures and the avatar, 2) different motion profiles of the animation, and 3) changes in the posture of the avatar (upper-body inclination). The experimental task consisted of a weight lifting task in which participants had to order four virtual dumbbells according to their virtual weight. The user had to lift each virtual dumbbells by means of a tangible stick, the animation of the avatar was modulated according to the virtual weight of the dumbbell. The results showed that the altering the spatial mapping delivered the best performance. Nevertheless, participants globally appreciated all the different visual effects. Our results pave the way to the exploitation of such novel techniques in various VR applications such as sport training, exercise games, or industrial training scenarios in single or collaborative mode.